Editing for Access: Practices and Reflections - Bartlett, Amorena; Acton, Kelsie; Percy, Graham; Hansen, Pil (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2025)
This article describes the approach to editing for access that was developed for the “Dramaturgies of Accessibility” issue of Performance Matters from 2024 to 2025. This approach was designed to be sustainable for independent publishers and strengthen a diverse community of knowledge. Sustainability is achieved by making resource-based choices about the forms of access provided and by distributing access work within a community while enabling each contributor to match their efforts to their capacity. This article shares examples of access guidelines for authors, kind peer review guidelines, and the practical steps of creating access materials. The authors transparently describe, and reflect on, their experiences editing for access to inspire other publishers and editors.